2012
DOI: 10.1136/annrheumdis-2011-201131
|View full text |Cite
|
Sign up to set email alerts
|

TLR9 agonist CpG enhances protective nasal HSP60 peptide vaccine efficacy in experimental autoimmune arthritis

Abstract: These clinical and immunological data suggest the use of CpG as a potent adjuvant for mucosal peptide-specific immune therapy in arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 82 publications
0
19
0
Order By: Relevance
“…Thus activation of pDCs through TLR9 is reported to be a normal, physiological response to DNA released in membrane microparticles from apoptotic cells (1553). CpG ODNs able to activate Th1 responses in some settings may also promote immune tolerance through Treg with enhanced IL-10 production in other contexts (541,2122). Perhaps further understanding of these complexities may help explain why in another study, depletion of pDC using a different anti-BST2 antibody was reported to increase carotid atherosclerosis induced by colar placement in LDLR null mice.…”
Section: Neutrophils May Interact With Plasmacytoid Dcs To Enhance Atmentioning
confidence: 99%
“…Thus activation of pDCs through TLR9 is reported to be a normal, physiological response to DNA released in membrane microparticles from apoptotic cells (1553). CpG ODNs able to activate Th1 responses in some settings may also promote immune tolerance through Treg with enhanced IL-10 production in other contexts (541,2122). Perhaps further understanding of these complexities may help explain why in another study, depletion of pDC using a different anti-BST2 antibody was reported to increase carotid atherosclerosis induced by colar placement in LDLR null mice.…”
Section: Neutrophils May Interact With Plasmacytoid Dcs To Enhance Atmentioning
confidence: 99%
“…Specifically, M cells in Peyer's patches take up luminal antigens to be presented to naive T cells in a controlled manner, which promotes their differentiation into a regulatory function . Thus, induction of adequate mucosal tolerance requires both colonization of beneficial microbes and interplay between innate and adaptive arms of the immune system and based on experimental studies, failure in this maturation process can predispose to autoantibody formation and arthritis…”
Section: The Microbiota and Immunologic Maturationmentioning
confidence: 99%
“…The hydrogel contained PLGA microparticles encapsulating denatured insulin to promote self-tolerance to recruited DCs and, notably, CpG. While CpG is more classically used as a vaccine adjuvant in an inflammatory capacity, the authors note it can elicit anti-inflammatory effects such as inducing IL-10 production [106]. This approach protected disease incidence in 40% of pre-diabetic mice.…”
Section: Controlled-release Approaches To Recruit Immune Cellsmentioning
confidence: 99%